Dolphin monitoring for enhancing metaheuristic algorithms: Layout optimization of braced frames. (March 2016) - Kaveh, A.; Farhoudi, N.
Highlights: Dolphin Monitoring (DM) is utilized to improve the performance of the metaheuristic algorithms. DM controls the progress of metaheuristic algorithms using some features of DEO rules. DM is incorporated in GA, ACO, PSO, BB-BC, CBO and ECBO. Three frames are studied to show how the use of DM improves the results. Abstract: In this study, Dolphin Monitoring (DM) is utilized to improve the performance of the metaheuristic algorithms for layout optimization of structures. DM is a method to control the progress of metaheuristic algorithms using some features of Dolphin Echolocation Optimization (DEO) rules. In the present work, DM is incorporated in GA, ACO, PSO, BB-BC, CBO and ECBO and applied to layout optimization of steel braced frames. Three frames are studied to show how the use of DM improves the results of the standard versions of all these algorithms.